The effect of polymer molecular weight and cell seeding density on viability of cells entrapped within PEGDA hydrogel microspheres. (4th July 2018) - Perera, Davina; Medini, Michael; Seethamraju, Deepika; Falkowski, Ron; White, Kristopher; Olabisi, Ronke M.
Abstract: Cell microencapsulation can be used in tissue engineering as a scaffold or physical barrier that provides immunoisolation for donor cells. When used as a barrier, microencapsulation shields donor cells from the host immune system when implanted for cell therapies. Maximizing therapeutic product delivery per volume of microencapsulated cells necessitates first optimising the viability of entrapped cells. Although cell microencapsulation within alginate is well described, best practices for cell microencapsulation within polyethylene glycol is still being elucidated. In this study we microencapsulate mouse preosteoblast cells within polyethylene glycol diacrylate (PEGDA) hydrogel microspheres of varying molecular weight or seeding densities to assess cell viability in relation to cell density and polymer molecular weight. Diffusion studies revealed molecule size permissible by each molecular weight PEGDA towards correlating viability with polymer mesh size. Results demonstrated higher cell viability in higher molecular weight PEGDA microspheres and when cells were seeded at higher cell densities.